CORRELATION BETWEEN SERUM CALCIUM AND PHOSPHATE WITH CORONARY ARTERY CALCIUM SCORES ON CARDIAC MSCT EXAMINATION - Kai, Rosita; Murtala, Bachtiar; Zainuddin, Andi Alfian; Amin, Muzakkir; Ilyas, Muhammad (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2019)
Increased serum calcium and phosphate associated with cardiovascular disease in patients with chronic kidney disease, but research on the relationship between coronary artery calcium scores with serum calcium and phosphate in individuals with normal kidney function is lacking. We explore the relationship of serum calcium and phosphate levels with coronary atherosclerosis as assessed by cardiac Multislice Computed Tomography (MSCT) in individuals with normal kidney function. This study aims to assess the correlation of calcium level scores on cardiac MSCT examination with serum calcium and phosphate levels, and assess the association with risk factors for coronary heart disease. This study was a cross-sectional study of 40 subjects who underwent cardiac MSCT examination with normal kidney function, at RSUP Dr. Wahidin Sudirohusodo Makassar during the March-July 2019 period. The results showed an correlation between coronary artery calcium scores with calcium and serum phosphate (serum calcium r = 0.67, serum phosphate r = 0.53, p <0.05).